先唐儒家“群”論的闡釋路徑與意義生成 - 周艷和; Zhou Yanhe (중국학보, 2025)
中國古代之“群”内涵豐富, 以經典話語為核心形成的闡釋路径奠定了儒家思想對“群”論的意義統 攝。受世代風會影響, 先唐不同階段關於“群”之闡釋有所差異。一是先秦時期, 從孔子到荀子的“群”義 闡發實現了“群”義由“從羊”轉向“從君”的意義凝定, 初步建構了“群”論的社會倫理及政治內涵；二是兩 漢時期, 經由漢人對“五經”文本的註解, “群”的政治教化意義得到極大彰顯, 塑造了“君者, 群也”的經 學言說立場；三是六朝時期, 根祇於儒道二家的“群”與“離群”之分化, 在詩學領域出現了“詩言志”與“詩 緣情”的情志分殊, 促使詩歌情感表現與審美旨趣由“詩可以群”走向“離群發怨”, 深刻影響了中國古典詩 學不同時期對集體意志與個體情感的軒輊取捨。不同維度的“群”論相互關聯, 全方位建構了儒家政治批 評與文學批評的觀念表達, 以小見大地展現出中國古代政治教化和詩歌情感的獨特進路與價值。 The concept of “qun” in ancient China possessed profound significance, with classical discourse serving as the core foundation for its interpretation, establishing the overarching dominance of Confucian thought regarding theories of “qun.” Shaped by prevailing ethos across different dynasties, interpretations of “qun” varied significantly throughout pre-Tang historical periods. Firstly, during the pre-Qin era, evolving philosophical discussions from Confucius to Xunzi transformed “qun” from its original connotation of following the ‘羊’ to a political ideal of following the ‘君’. This established its initial framework of social ethics and political value. Secondly, the Han Dynasty witnessed extensive commentaries on the “Five Classics,” which profoundly amplified “qun’s” significance in political indoctrination. This crystallized the Classicist assertion that “the ruler is the embodiment of the collective”. Thirdly, the Six Dynasties period saw a philosophical bifurcation rooted in Confucian and Daoist thought ― distinguishing between “belonging to the qun” and “separating from the qun”. This divergence manifested in poetics as the distinction between “poetry articulates intent” and “poetry arises from emotion”. Consequently, emotional expression and aesthetic orientation of poetry evolved from the normative “poetry can foster collectivity” toward an aesthetic of “solitary lament upon leaving the group”. This shift profoundly shaped the fluctuating prioritization of collective will versus individual emotion in classical Chinese poetics across eras. The theories of “qun” across different dimensions are interconnected, constructing a comprehensive framework for the expression of Confucian political criticism and literary criticism. This reveals, through specific insights into broader implications, the unique path and enduring value of ancient Chinese political edification and poetic sentiment transmission within Confucian doctrines.